Faktor-Faktor Yang Mempengaruhi Pendapatan Supir Angkutan Umum Antar Kabupaten Di Provinsi Papua Barat (Studi Kasus: Mobil Hilux Dan Triton) - Johny Aninam; Irawati; Naftali Mansim (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2022)
Abstract This study aims to see how much the income of inter-regency public transport drivers in West Papua Province is, and what factors influence the income of inter-regency public transport drivers. For the sample of inter-district public transport drivers as many as 54 drivers. This study uses a quantitative method, the source of the data in this study comes from interviews distributing questionnaires. This study uses multiple linear regression analysis tools. In this study, it is known that the income of inter-district drivers for one month varies from the lowest Rp. 4,000,000 and the highest income is Rp. 8,000 000. The number of hours worked, the number of passengers, and the fare have a significant and positive effect on the income of inter-district public transport drivers. Keywords: Income, number of hours worked, number of passengers, fares